Islamic Rural Bank Performance Model in Indonesia - Soleh, Soleh; Noor, Juliansyah (Jurnal Keuangan dan Perbankan, 2021)
The study aims to confirm research model the research model to specify how corporate culture mediates the influence of leadership skills on Islamic rural bank performance (iRBP). A special questionnaire designed for leaders, employees and customers was used to confirm the proposed model. Furthermore, the data set was composed of perceptions from 264 iRBP leaders, 463 customers, and 327 employees from the iRBP community in Indonesia. Also, structural equation modeling was used for data analysis. Although the results indicated that leadership skills have no significant direct influence on iRBP, it significantly influences iRBP through corporate culture. Therefore, this study examined how leadership skills improve iRBP, although it specifically focused on the banking industry. In addition, it still redounds to the literature by indicating the significance of corporate culture. DOI : https://doi.org/10.26905/jkdp.v25i2.5281